PUBLIC-PRIVATE PARTNERSHIP IN THE COUNTRIES OF THE EURASIAN ECONOMIC UNION - IVANOV, Oleg; ZAVYALOVA, Elena; RYAZANTSEV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2019)
The paper systematizes and examines the primary elements of the PPP management sphere in the countries of the Eurasian Economic Union (EAEU). These include doctrinal policy execution, long-term planning of infrastructure development, legislative support, establishing management bodies, key directions, and state support instruments. Based on relevant experience, recommendations are provided on the viability of raising the efficiency of PPP state management in EAEU countries and establishing cooperation between them in the PPP sphere. Recommendations are relevant, in particular, to the development of the PPP Institute based on a systemic approach, strategic infrastructure development planning, improvement of legislative regulation, strengthening mutual cooperation in the PPP sphere via the harmonization of regulatory and methodological framework, and integrating efforts in the implementation of trans-border infrastructure projects.